CORRELATION OF OXIDATIVE STRESS MARKERS MALONDIALDEHYDE (MDA), ANTIOXIDANT VITAMINS A, E, AND C WITH GLYCATED HEMOGLOBIN (HBA1C) LEVELS IN TYPE 2 DIABETES MELLITUS - Altoum, Abd Elgadir A.; Osman, Ahmed L.; Babker, Asaad Ma. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of this study was to understand the relationship between oxidative stress markers malondialdehyde (MDA), antioxidant Vitamins A, E, and C and the glycated hemoglobin levels with Type 2 diabetes mellitus. Methods: The current study is a cross-sectional study group, comprised no diabetic individuals (100 healthy) as control groups and diabetic patients (300) as cases groups, attending the Khartoum - Sudan for routine follow-up during 2013â€“2015. The data were collected with the help of structured questionnaire and direct interview to collect information. Blood specimens were collected from both groups, and plasma levels of MDA, serum zinc, antioxidant Vitamins (A, E, and C), and glycated hemoglobin (HbA1c) were determined. Odds ratio and the 95% confidence interval (95% CI) were calculated for the presence of mutation between cases and controls and analyzed by SPSS program, version 13. Results: The results of this study indicate a highly significant difference between the means of HbA1c% of the test group (n=300) and the control group (n=100). Mean Â± SD: 7.5 Â± 1.4 versus 4.9 Â± 0.3, respectively (p=0.001). Significant positive correlation between HbA1c and MDA (p=0.003). Significant correlation between HbA1c% and plasma Vitamins A, E, and C of the test group, respectively (p=0.002), (p=0.0008), and (p=0.01). Conclusion: There was significant correlation between HbA1c% with Malondialdehyde (MDA) and antioxidant Vitamins (A, C, and E).Â